Securing a cloud storage system with social-networking capabilities - Yeo, Alwyn. (2012)
In recent years, “Cloud” computing has become the new buzzword amongst the IT community. Surveys have estimated that the size of this market will reach a startling US$160 billion by 2013 (Ingthorsson, 2011). The advancement in internet infrastructure across the globe has helped catalyzed the evolution of this trend. With the growing popularity of cloud computing, security has become an increasing concern amongst users. Cloud storage, being an extension of cloud computing, faces similar issues that are preventing its proliferation of usage. As such, the purpose of this project is to address the security concerns that are hindering the widespread adoption of such a storage option.The project focuses on the development of an entirely new “Cloud” storage system that utilizes up to date encryption standards and is backed by a “zero knowledge” server. This secured encrypted environment will give users the assurance to embrace such a storage solution. Furthermore, to differentiate this storage application from those available in the market, the application has integrated unique social networking functions which enable group file sharing, instant messaging and many others, within the same secured environment.